Prioritization of Iranian Male Mental Disorders Based on latest Prevalence, Burden, Male/Female Ratio and Expert Pane; a Systematic Review - Hajebi, Ahmad; Aliakbari, Fereshteh; Shojaeefar, Ehsan; Hosseini, Mohammad Ali (Archives of Men's Health, 2021)
Introduction: Mental disorders are the most prevalent health problems in the world. 23.6% of Iranians have at least one psychological disorder. Men usually neglect their mental health issues, and their top priority mental health disorders should be determined for health planning. Methods: International databases including MedLine, Scopus, Web of Science, ProQuest, and SID national database were searched from 2015 to October 2020. The latest reported prevalence and percent of total DALY (Disability-adjusted life year), their difference between sexes as well as the expert panel’s opinion about mental disorders were gathered in a matrix based on the Three-Dimensional Combined Approach Matrix (3D-CAM). Each item got a rank and prioritization was made base on mean rank. Results: Eight studies were included. The most prevalent mental disorders among the Iranian male population were Major Anxiety Disorders (MADs, 12%) and the highest burden belonged to Major depressive disorder (MDD) comprising 2.88% of the total DALY. Considering all parameters, the highest priority was the Drug Use Disorders (DUD) followed by Alcohol Use disorders (AUDs), Conduct disorder, MADs, Bipolar disorder, MDD, and Schizophrenia, respectively. Conclusion: Men are extremely affected by drug and alcohol use disorders in Iran and also there is a lack of practical screening and effective interventional programs for these disorders in the primary health care system. More intensive harm reduction programs are needed for decreasing devastating consequences of any substance use disorders as well as improving mental health literacy and raising awareness toward risk perception for preventive and controlling purposes.